CFD Simulation of Methanol Dehydration Step through an Adiabatic Fixed-bed Reactor of DME Synthesis - Mofidian, Roozbeh; Jahanshahi, Mojtaba; Hosseini, Seyed Sharafoddin; Miansari, Mehdi (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Today, dimethyl ether (DME) is changing to ordinarily worn as a superb aerosol propellant and refrigerant for its eco-friendly characteristics. Lately, with the development of novel chemical energy in the coal industries, it has become a fascinating field of research as an alternative green fuel for diesel machines due to the high cetane number. The DME synthesis processes include catalytic dehydrating methanol in an adiabatic fixed-bed reactor. In this study, to investigate the chemical conditions of the methanol dehydration reaction, CFD simulations of the adiabatic reactor have been assessed. The advantage of the work is a sensitivity analysis was run to find the effect of pressure, kinetics, and velocity on the reactor performance. The results showed that using a γ-Al2O3 catalyst with selective mechanical properties and unique surface properties is a convenient choice for DME synthesis. The CFD simulation results also show that the laboratory data such as pressure, energy, and velocity in the adiabatic reactor meet the reaction requirements well, and deliberated a major vision of what happened in the reactor. Also, the graphs of the temperature profile with changes in physical properties pomp that methanol dehydration reaction strongly depends on environmental factors and gives different results under the influence of other conditions.